The effects of sertraline administration from adolescence to adulthood on physiological and emotional development in prenatally stressed rats of both sexes - Pereira-Figueiredo, Inês (Frontiers Media S.A., 2014)
Sertraline (SERT) is a clinically effective Selective Serotonin Reuptake Inhibitor (SSRI) known to increase and stabilize serotonin levels. This neurotransmitter plays an important role in adolescent brain development in both rodents and humans, and its dysregulation has been correlated with deficits in behavior and emotional regulation. Since prenatal stress may disturb serotoninergic homeostasis, the aim of this study was to examine the long-lasting effects of exposure to SERT throughout adolescence on behavioral and physiological developmental parameters in prenatally stressed Wistar rats. SERT was administered (5 mg/kg/day p.o.) from the age of 1–3 months to half of the progeny, of both sexes, of gestating dams stressed by use of a restraint (PS) or not stressed. Our data reveal that long-term SERT treatment slightly reduced weight gain in both sexes, but reversed the developmental disturbed “catch-up” growth found in PS females. Neither prenatal stress nor SERT treatment induced remarkable alterations in behavior and had no effects on mean startle reflex values. However, a sex-dependent effects of PS was found: in males the PS paradigm slightly increased anxiety-like behavior in the open field, while in females, it impaired startle habituation. In both cases, SERT treatment reversed the phenomena. Additionally, the PS animals exhibited a disturbed leukocyte profile in both sexes, which was reversed by SERT. The present findings are evidence that continuous SERT administration from adolescence through adulthood is safe in rodents and lessens the impact of prenatal stress in rats.